Entrepreneurial initiatives as a microfoundation of dynamic capabilities. Issue 1 (5th March 2018) - Mahringer, Christian A.; Renzl, Birgit
Abstract : Purpose: The purpose of this paper is to show how entrepreneurial initiatives in organizations serve as a microfoundation of dynamic capabilities and, thus, foster change in organizations. Design/methodology/approach: This paper revises and applies conceptual and empirical research on dynamic capabilities, their microfoundations and corporate entrepreneurship. In addition, it develops a model of how entrepreneurial initiatives, operative routines and capabilities interact. Findings: The paper develops a model of how entrepreneurial initiatives in organizations represent a microfoundation of dynamic capabilities. First, the model shows that environmental dynamism reduces fit of operative routines and capabilities. Second, the model states that entrepreneurial initiatives are triggered by operative routines and capabilities with respect to environmental dynamism. Third, the model suggests that entrepreneurial initiatives disrupt operative routines and capabilities and, thus, restore their fit in dynamic environments. The paper contributes to current research on dynamic capabilities, their microfoundations and corporate entrepreneurship. Originality/value: This paper addresses the tension between routinization and the entrepreneurial nature of dynamic capabilities. Considering entrepreneurial initiatives as a microfoundation shows that dynamic capabilities might be entrepreneurial, but still preserve their patterned nature enabling repeated execution. This approach provides a way to reconcile the two sub-streams in dynamic capability research and preserve their ontological assumptions. Moreover, this paper extends the literature on dynamic capabilities by ascertaining how individual and group level entrepreneurial initiatives operate within a broader context.